Hey there, it's Yogi Bear! - Hanna, William, 1910-2001.; Barbera, Joseph; Butler, Daws.; Bennet, Julie; Messick, Don.; Blanc, Mel.; Warner Home Video (Firm) ([United States] : Warner Home Video, 2008)
Between bouts of wit with Ranger Smith, Yogi juggles a little romance with Cindy Bear. Because of her fondness for Yogi, Cindy finds herself the victim of an evil circus director. It's up to Yogi and his sidekick Boo Boo to save her.
Title from container.
Originally produced as a motion picture in 1964.
Voices: Daws Butler (Yogi bear), Julie Bennet (Cindy), Don Messick (Boo Boo/Ranger Smith), Mel Blanc (Grifter), J. Pat O'Malley (Snively), Hal Smith (Corn Pone).
MPAA rating: G.
DVD.
English or Portuguese audio; English or Portuguese subtitles; English subtitles for the deaf and hard of hearing.
Keywords: Bears -- Juvenile films; Feature films; Children's films; Animated films; Fiction films; Video recordings for the hearing impaired; Portuguese language materials